2017
DOI: 10.1084/jem.20160652
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 supports pulmonary microvascular integrity by linking vascular endothelial cadherin and protein tyrosine phosphatases

Abstract: Luo et al. demonstrate that annexin A2 is required to maintain vascular integrity in the hypoxic mouse lung. A2 prevents extravasation of fluid and leukocytes by promoting activity of the phosphatases VE-PTP and SHP2, thereby modulating phosphorylation of vascular endothelial cadherin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…Consistently, an earlier study reported that AnxA2 expression was increased after traumatic spinal cord injury [17]. The most important finding of the present study is the association of AnxA2 deficiency with the increased leukocyte brain infiltration, which is consistent with previous studies showing that A2KO mice exhibit increased pulmonary neutrophil infiltration in polymicrobial sepsis models [14] as well as in response to subacute alveolar hypoxia [18] compared to WT mice. Two potential mechanisms are underlying the role of AnxA2 in regulating leukocytes brain infiltration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistently, an earlier study reported that AnxA2 expression was increased after traumatic spinal cord injury [17]. The most important finding of the present study is the association of AnxA2 deficiency with the increased leukocyte brain infiltration, which is consistent with previous studies showing that A2KO mice exhibit increased pulmonary neutrophil infiltration in polymicrobial sepsis models [14] as well as in response to subacute alveolar hypoxia [18] compared to WT mice. Two potential mechanisms are underlying the role of AnxA2 in regulating leukocytes brain infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, the increased leukocytes infiltration might also be at least partially attributed by the BBB integrity disruption in the A2KO mice. There were previous reports of increased pulmonary neutrophil infiltration in A2KO mice during alveolar hypoxia, which is associated with a reduced endothelial barrier function compared to the WT mice [18]. Moreover, we recently reported that A2KO mice compromise brain microvascular integrity [16].…”
Section: Discussionmentioning
confidence: 84%
“…Microvascular endothelial cells deficient in annexin A2 exhibit reduced barrier function. 21 Annexin A2edeficient mice develop more substantial vascular leak, pulmonary edema, and neutrophil infiltration in response to alveolar injury compared with control mice. 21 Annexin A2 can bind to actin and bundle actin filaments through residues on its C-terminus, and it also interacts directly with VE-cadherin in endothelial cells.…”
mentioning
confidence: 98%
“…While the roles of EPAC signaling in modulating endothelial barrier functions and inflammatory response have been examined extensively (22,23), studies and information related to cAMP's functions in fibrinolysis are scarce. Our current study reveals that EPAC1 interacts with AnxA2, a phospholipid binding protein abundantly expressed in endothelial cells and important for vascular fibrinolysis and integrity (24,25). This unexpected finding led us to investigate the physiological functions of EPAC1:AnxA2 interaction.…”
Section: Discussionmentioning
confidence: 60%